Distribuição geográfica de Psychosaura agmosticha (Rodrigues, 2000) (Squamata, Mabuyidae) - Arnaldo Magalhães Júnior; Leonardo Barros Ribeiro; Patrícia Avello Nicola; Luiz Cezar Machado Pereira; Severino Mendes Azevedo Júnior (Biotemas)
http://dx.doi.org/10.5007/2175-7925.2014v27n2p217